Relationship between Viral Load Levels and Malnutrition Screening and Nutritional Status in HIV Patients at RSUD Dr. M Yunus Bengkulu - Oktavia Salsadillah Putri; Enny Nugraheni; Noor Diah Erlinawati; Mulya Sundari; Debie Rizqoh (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) cases continue to increase and are becoming a top global public health problem. When weight loss is more than 10% below the previous body weight, the relative risk of death is going to increase almost 6-fold. A viral load checkup is a test to measure the amount of HIV in the blood. The increase in nutritional needs and tissue catabolism is caused by the increase in viral load in the body. Malnutrition screening is necessary to evaluate nutritional status so that this treatment can be recommended if the patient is malnourished. This research is an analytical observational study with a cross-sectional design. Analysis was carried out on 109 people living with HIV who received treatment at RSUD Dr. M Yunus Bengkulu. The independent variable in this study is the viral load level, while the dependent variable is screening for malnutrition and the nutritional status of people living with HIV/AIDS—data analysis using the Spearman Rank test. The study results showed no correlation between viral load levels and nutritional status with a value of p=0.243 (p>0.05), and there was a correlation between viral load levels and malnutrition screening with p≤001. The viral load of HIV patients at Dr. M Yunus Bengkulu does not correlate with nutritional status, but it correlates with malnutrition screening.